Correctness of the transformation: transformation of ontology axioms in formal rules - Vasilecas, Olegas; Būgaitė, Diana (Lietuvos matematikos rinkinys, 2021)
In this paper, authors emphasise on the correctness of the transformation. Therefore, types of correctness are analysed here. As a context of transformation, the transformation of PAL constraints in SQL rules is chosen for more details. Formal rules for the transformation of PAL constraints in SQL rules are presented in this paper also. And finally, the analysis of the proposed transformation is checked.